Phenotypic Craniofacial and Upper Spine Characteristics in Patients with Obstructive Sleep Apnoea - Anne Marie Aavang Arvidson; Liselotte Sonnesen (Dentistry Journal)
Background/Objectives: This study investigates differences in craniofacial morphology including skull thickness, sella turcica morphology, nasal bone length, and posterior cranial fossa dimensions, as well as differences in head posture and deviations in upper spine morphology, in adult OSA patients compared to healthy controls with neutral occlusion. Methods: 51 OSA patients (34 men, 17 women, mean age 51.9 ± 11.3 years) and 74 healthy controls (19 men, 55 women, mean age 38.7 years ± 14.0 years) with neutral occlusion were included. Craniofacial morphology and head posture were investigated using cephalometric measurements on lateral cephalograms and morphological deviations in sella turcica and upper spine were assessed through visual description of lateral cephalograms. Results: OSA patients had significantly more retrognathic maxilla (p = 0.02) and mandible (p = 0.032 and p = 0.009), significantly larger beta-angle (p = 0.006), and significantly smaller jaw angle (p = 0.045) compared to controls. OSA patients had significantly larger length (p = 0.003, p = 0.001, p = 0.044) and depth of the posterior cranial fossa (p < 0.001) compared to controls. OSA patients had a significantly more extended (p < 0.001) and forward-inclined head posture (p < 0.001) and morphological deviations in the upper spine occurred significantly more often in OSA patients compared to controls (p = 0.05). No significant differences in skull thickness, nasal bone length, and morphological deviations in the sella turcica (p = 0.235) were found between the groups. Conclusions: Significant deviations were found in craniofacial morphology, head posture, and morphological deviations in the upper spine. The results may prove valuable in the diagnostics of OSA patients and in considerations regarding etiology and the phenotypic differentiation of OSA patients.